2009
DOI: 10.1080/00016340903134171
|View full text |Cite
|
Sign up to set email alerts
|

Selective prophylactic transfusion in sickle cell disease

Abstract: OBJECTIVE. To record feto-maternal complications following the use of selective prophylactic transfusions in women with major sickle cell disease (SCD) and determine whether selective prophylactic transfusion reduces these complications, through a comparison with a population of women who received transfusions for complications only. DESIGN. A retrospective cohort study. SETTING. Public regional referral hospital in western French Guyana. POPULATION. Between 1992 and 2004, in all 29 women, 55 pregnancies, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…A recent meta‐analysis on pregnancy in SCD supports the positive impact of a prophylactic transfusion regimen on sickle cell–related clinical manifestations with an improvement of maternal morbidity but with limited effect on IUGR . Partial red blood cell (RBC) exchange or automatic erythrocytapheresis (ECP) have also been reported to be relevant in management of SCD women during pregnancy, also improving perinatal outcomes . In these studies, ECP was started at different time of pregnancy, ranging from 22 to 28 weeks of gestation.…”
supporting
confidence: 73%
“…A recent meta‐analysis on pregnancy in SCD supports the positive impact of a prophylactic transfusion regimen on sickle cell–related clinical manifestations with an improvement of maternal morbidity but with limited effect on IUGR . Partial red blood cell (RBC) exchange or automatic erythrocytapheresis (ECP) have also been reported to be relevant in management of SCD women during pregnancy, also improving perinatal outcomes . In these studies, ECP was started at different time of pregnancy, ranging from 22 to 28 weeks of gestation.…”
supporting
confidence: 73%
“…Despite prophylactic transfusions, preeclampsia was higher in the SS group than among controls (9.4% vs. 2.3%, p = 0.03) . In a French cohort, women who had received prophylactic transfusions had lower rates of vasoocclusive crisis (p = 0.002) and preterm deliveries (p = 0.036); unexpectedly, however, there was a significant increase in cases of intrauterine growth restriction (p = 0.048) …”
Section: Discussionmentioning
confidence: 98%
“…A significant decrease in maternal mortality and in the incidence of vasoocclusive crisis between patients undergoing prophylactic transfusions and control groups has also been demonstrated . Another retrospective cohort involving 55 pregnancies showed that women who had received prophylactic transfusions had lower rates of vasoocclusive crisis and preterm deliveries, although no improvement regarding intrauterine growth restriction was established …”
mentioning
confidence: 98%
“…Exchange transfusions replace sickled RBCs with normal RBCs without altering blood viscosity and, consequently, improve delivery of oxygen to oxygen-deprived tissues. The decision for simple or exchange transfusion ideally should depend on the severity of the situation (6,13). Exchange transfusion is recommended in the treatment of severe complications such as ACS, stroke and multi-organ failure in patients with SCD.…”
Section: Casementioning
confidence: 99%